Analytical documentation of an Arabian horse fatality related to Oenanthe crocata poisoning. (30th April 2022) - Gish, Alexandr; Robveille, Cynthia; Gicquel, Thomas; Allorge, Delphine; Gault, Gilbert; Gaulier, Jean-Michel
Abstract: Analytical detection of Oenanthe crocata toxins in biological samples is challenging because of their instability, the lack of commercially available standards and the exceptionally low detection of these molecules using mass spectrometry. This work aims to report the used analytical methods that allowed identification of the main plant toxins in biological samples from an equid (an Arabian horse) fatality related to hemlock water dropwort ( Oenanthe crocata Linnaeus ) intake. Using both LC-DAD and LC-HRMS methods allowed identification (i) of oenanthotoxin in roots found on the site, root fragments found in the stomach, stomach content, kidney, and liver, and (ii) of the hydrogenated metabolite of oenanthotoxin (2, 3-dihydro-oenanthotoxin) in roots found on the site, root fragments found in the stomach, stomach content, kidney, liver and spleen. Reported analytical data about Oenanthe crocata toxins can be useful for identification of the ingested plant and for supporting a poisoning diagnosis in such cases. Graphical abstract: Image 1 Highlights: A poisoning case of a horse related to Hemlock Water Dropwort ( Oenanthe crocata ) with post-mortem diagnosis is reported. Toxin (oenanthotoxin and 2, 3-dihydro-oenanthotoxin) identifications were performed in post-mortem samples. A combination of LC-DAD and LC-HMRS methods was used for identification of the two toxins.